Implementasi Metode Vikor Dalam Perekrutan Pegawai Tetap dan Cadangan Pada Mandali Packaging - Lubis, Farhan Rusdy Asyhary; Kurniawan, Rakhmat (Journal of Computer System and Informatics (JoSYC), 2024)
Today's technological advances are rapidly expanding, which opens up a huge opportunity for entrepreneurs to implement and develop a recruitment system for prospective employees as an effective and efficient means of promoting performance. Decision-making using technology makes the decision-making process run faster and more accurate. Mandali Packaging is a business model that moves in the field of creative industries, precisely in the sablon service that still implements the recruitment process of staff manually. The aim of this research is to implement and develop a decision support system using the VIKOR method to improve the effectiveness and objectivity of the recruitment process in Mandali Packaging. The method is used because it has the ability to solve multi-criterion problems, provide optimal solutions based on the preference of the established criteria, and also help reduce the bias of subjectivity that often occurs in manual decision-making. The ranking results show that Ali Imron Lubis received the 1st rank with the lowest score of 0 because in the VIKOR method, the lower the score, the higher the rank. This research demonstrates that the VIKOR method has the potential to provide more accurate and objective recommendations.